Implementation Of Constituent Recall Of Political Officers In Indonesia As An Effort To Strengthen The Principle Of People's Sovereignty - Nurdin, Nurdin; Prabu Buana Rumiartha, I Nyoman (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
In Indonesia, the idea of recall has only ever been used by political parties; hence, the general populace has never been given the opportunity to participate in the recall procedure (also known as a constituent recall) for members of the DPR and DPRD who have been directly elected by the people. This is problematic due to the fact that it does not adhere to the democratic values and the notion of people sovereignty that are stipulated by the 1945 Constitution of the Republic of Indonesia. As a result, it is not in conformity with these principles. Doctrinal research is the research technique that was used in this study. Doctrinal research is defined as research that investigates laws that are conceptualised and produced based on the doctrines that are adhered to by the conceptualizers or formulators. This kind of study also falls under the category of normative research. The notion of political party recall rights is the subject of the study that is referred to in this research.